2018
DOI: 10.1177/2058738418798249
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical evaluation of mandibular bone tissue regeneration

Abstract: The purpose of the study was to perform an immunohistochemical and histological evaluation of samples taken from different bone regeneration procedures in atrophic human mandible. 30 patients (15 men and 15 women, age range of 35–60 years), non-smokers, with good general and oral health were recruited in this study and divided into three groups. The first group included patients who were treated with blood Concentration Growth Factors (bCGF), the second group included patients who were treated with a mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Characteristic of carbonate bands also observed at 1415,1462 and 875 cm- 1 and sample confirm the formation of carbonated apatite type A and B as shown by the peak at 1417 cm -1 , 1412 cm -1 and type B carbonates at the peak 1415 cm -130 as showed in Fig, 2 XRD pattern showed the sample consist of pure hydroxyapatite phase according to PDF 2.841998 The hydroxyl apatite in CHA is shown by three main peak of the hydroxyapatite phase angles 2θ of 31.80°, 32.23°, and 32.96°, corresponding to the (121), (112), and (300) crystal plane of the hexagonal structures of hydroxyl apatite as showed in Fig. In vitro fibroblast cell viability test showed that the number of living cells above 80% and no morphological changes.…”
Section: Mechanical Properties and Characterization Of Geopolymer-carmentioning
confidence: 82%
See 1 more Smart Citation
“…Characteristic of carbonate bands also observed at 1415,1462 and 875 cm- 1 and sample confirm the formation of carbonated apatite type A and B as shown by the peak at 1417 cm -1 , 1412 cm -1 and type B carbonates at the peak 1415 cm -130 as showed in Fig, 2 XRD pattern showed the sample consist of pure hydroxyapatite phase according to PDF 2.841998 The hydroxyl apatite in CHA is shown by three main peak of the hydroxyapatite phase angles 2θ of 31.80°, 32.23°, and 32.96°, corresponding to the (121), (112), and (300) crystal plane of the hexagonal structures of hydroxyl apatite as showed in Fig. In vitro fibroblast cell viability test showed that the number of living cells above 80% and no morphological changes.…”
Section: Mechanical Properties and Characterization Of Geopolymer-carmentioning
confidence: 82%
“…Bone healing event after implant placement is preceded by several stages until osseointegration occurs, which characterized by close contact between the implant surface and the surrounding bone. 1,2,3 Currently, titanium and zirconia are the most widely used as dental implant materials due to their biocompatibility and mechanical properties. However, there is disadvantage the elastic modulus of titanium (2222.7 ± 277.6 MPa) and zirconia (90 GPa) values are greater than enamel (1338.2 ± 307.9 MPa) and dentin (1653.7±277.9 MPa), less bioactive to stimulate osseointegration even the surface has been modified.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative method to assess such parameters exists, as shown by the studies of Zhihua Han et al [ 39 ], however, this has been done on large scale tissue samples in humans and it was not feasible for our study. Also, using Widmer’s hot spot method to quantify histological structures, such as osteoblasts, osteocytes, etc., requires immune-staining techniques that have not been performed in our study [ 40 ].…”
Section: Limitations Of the Current Studymentioning
confidence: 99%
“…The rats were buried according to experimental animal guidance. The mandible in the incisive region were cut vertically, and made into a paraffin block [12].…”
Section: Tissue Collectionmentioning
confidence: 99%
“…The slides were subsequently stained using hematoxylin and eosin (HE). The angiogenesis rate was observed under a light microscope at 400x magnification [12].…”
Section: Histological Examinationmentioning
confidence: 99%